PEDAGANG KAKI LIMA DI PASAR PEUNAYONG KOTA BANDA ACEH (SUATU TINJAUAN HISTORIS TAHUN 2003-2015) - Rizki Noviyuanda; Husaini .; Anwar Yoesoef (Universitas Syiah Kuala, 2018)
ABSTRACTPeunayong Market is one of the biggest markets in Banda Aceh city. The study, entitled